To solve the equation \(4(x - 4) = x - 13\) using inverse operations, follow these steps:
-
Distribute the 4 on the left side: \[ 4x - 16 = x - 13 \]
-
Isolate the variable terms on one side: Subtract \(x\) from both sides. \[ 4x - x - 16 = -13 \] This simplifies to: \[ 3x - 16 = -13 \]
-
Isolate the constant: Add 16 to both sides. \[ 3x - 16 + 16 = -13 + 16 \] This simplifies to: \[ 3x = 3 \]
-
Solve for \(x\): Divide both sides by 3. \[ x = \frac{3}{3} \] Thus: \[ x = 1 \]
Conclusion
The solution to the equation \(4(x - 4) = x - 13\) is \(x = 1\).
If you need to visualize this using sketch pad or paper, you can organize your work in a similar structured format as shown above, or use graphical representations to depict the operations performed. If you would like to upload or share your sketch, please do so.